1999
DOI: 10.1074/jbc.274.46.32543
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel PSD-95/Dlg/ZO-1 (PDZ)-like Protein Interacting with the C Terminus of Presenilin-1

Abstract: Presenilin-1 (PS-1) is the most causative Alzheimer gene product, and its function is not well understood. In an attempt to elucidate the function of PS-1, we screened a human brain cDNA library for PS-1-interacting proteins using the yeast two-hybrid system and isolated a novel protein containing a PSD-95/Dlg/ZO-1 (PDZ)-like domain. This novel PS-1-associated protein (PSAP) shares a significant similarity with a Caenorhabditis elegans protein of unknown function. Northern blot analysis revealed that PSAP is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 25 publications
(29 reference statements)
3
33
0
Order By: Relevance
“…Is the mitochondrial localization sufficient for the pro-apoptotic activity of PSAP? In this regard, it is notable that PSAP was thought to contain a putative PDZ domain [10] and that this putative PDZ domain remains intact in mutant NPDZ. Thus, we created a ΔCPDZ mutant in which, in addition to the Cterminal 67 amino acids, the PDZ domain was also deleted, and it was found that the proapoptotic activity of PSAP was completely abolished, though this mutant was still localized in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Is the mitochondrial localization sufficient for the pro-apoptotic activity of PSAP? In this regard, it is notable that PSAP was thought to contain a putative PDZ domain [10] and that this putative PDZ domain remains intact in mutant NPDZ. Thus, we created a ΔCPDZ mutant in which, in addition to the Cterminal 67 amino acids, the PDZ domain was also deleted, and it was found that the proapoptotic activity of PSAP was completely abolished, though this mutant was still localized in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, as in the case of PS2, the C-terminal fragment of PS1 was also found to inhibit Fas-induced apoptosis in Jurkat cells [9]. In an effort to understand the apoptotic regulatory effect of the C-terminal of PS1, we have identified a novel presenilin-associated protein (PSAP), which interacts with the C-terminal of PS1 [10]. Interestingly, in a subsequent study we found that PSAP is a pro-apoptotic protein that causes apoptosis when it is overexpressed [11].…”
Section: Introductionmentioning
confidence: 99%
“…CD47ec-CD7 mutants and wild-type CD47 transfected cells showed comparable levels of Fas-induced apoptosis (result not shown). Note that the use of MMS domain as bait to perform the two-hybrid screen has already been successively performed (31)(32)(33)(34)(35)(36). In the present screen, five positive clones were selected of an estimated 5 ϫ 10 6 colonies, for their ability to reconstitute a functional Gal4 transcription complex.…”
Section: Cd47 Induces a Rapid Mitochondrialmentioning
confidence: 99%
“…This may be largely because, in contrast to PS1, PS2 does not interact with PSAP, as reported in our previous study (16).…”
Section: Discussionmentioning
confidence: 52%
“…Using a yeast two-hybrid system, our previous study identified PS1-associated protein (PSAP); this protein was subsequently found to be a mitochondrial proapoptotic molecule (16,17). This finding provides a direct molecular link between PS1 and the apoptotic pathway and opens a new avenue for studying the molecular mechanism by which PS-1 regulates apoptosis.…”
mentioning
confidence: 93%